PEMBELAJARAN BAHASA ARAB : PROBLEMATIKA DAN SOLUSINYA - Fahrurrozi, Aziz (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
There are some factors influencing teaching and learning of foreign language. In teaching Arabic, for example, linguistic factors, such as Phonology, Grammatical rules, Morphology, and Vocabulary. Non linguistic factor also influences teaching and learning Arabic, for example, teaching aids, teaching method, age and environment. Teaching method in Arabic classroom is one of the important factor. This article discusses how linguistic factor and non linguistic factor influenced Arabic Classroom. DOI: 10.15408/a.v1i2.1137